Pengaruh Kualitas Produk, Persepsi Harga, dan Word of Mouth terhadap Keputusan Pembelian: (Studi pada Konsumen Dandyco Bakery Bintaro di Tangerang Selatan) - Azza Fadia Humayroh; Rina Ayu Vildayanti (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
The purpose of this study was to determine the Product Quality, Price Perception, and Word of mouth on purchasing decisions. The sample in this study were 100 consumers of the Dandyco Bakery Bintaro Consumers in South Tangerang. The sampling method using the non-probability sampling method with accidental sampling technique. Data collection by distributing questionnaires. The research instrument was a questionnaire with a Likert Scale. The method used in this research is quantitative method. The results of respondents' answers to the questionnaire given were then processed using SPSS version 26. The results showed that Product Quality, Price Perception and Word of mouth variables had a significant influence on purchasing decisions.